Natural Gas and Renewable Methane for Powertrains Future Strategies for a Climate-Neutral Mobility - van Basshuysen, Richard (Powertrain, 2016)
This book focuses on natural gas and synthetic methane as contemporary and future energy sources. Following a historical overview, physical and chemical properties, occurrence, extraction, transportation and storage of natural gas are discussed. Sustainable production of natural gas and methane as well as production and storage of synthetic methane are scrutinized next. A substantial part of the book addresses construction of vehicles for natural and synthetic methane as well as large engines for industrial and maritime use. The last chapters present some perspectives on further uses of renewable liquid fuels as well as natural gas for industrial engines and gas power plants.